Bioequivalence Assessment of Two Metformin Tablet Formulations Based on Urinary Excretion Data - Eva Troja (Pharmaceutical Science: New Insights and Developments Vol. 6, 2025)
Metformin is an oral antihyperglycemic agent that has been widely used in the management of type 2 diabetes mellitus for decades. Metformin is slowly absorbed after oral administration, and about 60% of an oral dose is excreted in the urine as unchanged drug within 24 h. The aim of the present study was to assess the bioequivalence of two metformin tablet formulations available in the Albanian market (product R as reference formulation and product T as test formulation). The bioequivalence study was performed in eighteen healthy volunteers in a two-treatment, open, crossover design. A single oral dose (tablet containing 850 mg of metformin) of each product was administered with one-week washout period. Urinary concentrations of metformin were measured by high-performance liquid chromatography (HPLC) method, and pharmacokinetic parameters were estimated by urinary excretion data. The bioequivalence was determined by the following parameters: the cumulative amount of metformin excreted in the urine, the total amount of metformin excreted in the urine and the maximum urinary excretion rate of metformin. Various pharmacokinetic parameters like peak excretion rate [(dDU/dt)max], time for peak excretion rate (tmax), cumulative amount (Dcum0-24), total amount of drug recovered from urine (Dcum0-\(∞\)), elimination half-life (t1/2), and terminal elimination rate constant (kel), were calculated for both the formulations. Student’s t-test (paired) at a 5% level of significance was used for testing the differences between the mean values obtained from two treatments using statistical software STATA 13. Pharmacokinetic parameters generated for the two treatments were also compared for significant differences using ANOVA. The average cumulative amounts of metformin excreted in urine after administration of Formulation R and Formulation T were found to be 346.3 mg (40.74% of dose) and 358.7 mg (42.2% of dose), respectively. The urinary excretion profiles of metformin up to 24 h for both formulations were found to be similar. Statistical comparison (90% confidence intervals of ratio) of pharmacokinetic parameters were in compliance with the international standards, indicating that products R and T can be considered bioequivalents and therefore interchangeable. The study also recommends conducting bioequivalence evaluations for other key medications listed in the national reimbursement list.